Lyrik. Gattungsgeschichte, Formen, Analysetechniken - Elit, Stefan

Stable governments and the semistrict core - Dimitrov, Dinko; Haake, Claus-Jochen (Games and Economic Behavior)

The Shapley value of phylogenetic trees - Haake, Claus-Jochen; Kashiwada, Akemi; Su, Francis Edward (Journal of Mathematical Biology)

Two support results for the Kalai–Smorodinsky solution in small object division markets - Haake, Claus-Jochen (Mathematical Social Sciences)

On Maskin monotonicity of solution based social choice rules - Haake, Claus-Jochen; Trockel, Walter (Review of Economic Design)

Extended Results on an Adaptive Resource/Performance Trade-Off for Resolving Complex Queries in P2P Networks - Biermann, Thorsten; Dannewitz, Christian; Karl, Holger

Comments on: Transversality of the Shapley value - Haake, Claus-Jochen (TOP)

SIGNUM: A Graph Algorithm for Terminology Extraction - Ngonga Ngomo, Axel-Cyrille (Computational Linguistics and Intelligent Text Processing, 9th International Conference, CICLing 2008, Haifa, Israel, February 17-23, 2008, Proceedings)

Knowledge-free discovery of domain-specific multiword units - Ngonga Ngomo, Axel-Cyrille (Proceedings of the 2008 ACM Symposium on Applied Computing (SAC), Fortaleza, Ceara, Brazil, March 16-20, 2008)

Vorwort - Eke, Norbert Otto (Werner Fritsch/Johanna Fritsch: Das Meer rauscht und rauscht – bis es lauscht. Hörstück)

Stefan Hulfeld: Theatergeschichtsschreibung als kulturelle Praxis. Wie Wissen über Theater entsteht. Zürich: Chronos, 2007 - Eke, Norbert Otto (Germanistik)

Lisa Marie Küssner: Sprach-Bilder versus Theater-Bilder. Möglichkeiten eines szenischen Umgangs mit den „Bilderwelten“ von Werner Fritsch. Marburg: Tectum, 2006 - Eke, Norbert Otto (Germanistik)

Stefanie Watzka: Verborgene Vermittler. Ansätze zu einer Historie der Theateragenten und -verleger. Marburg: Tectum, 2006 - Eke, Norbert Otto (Germanistik)

Olaf Briese: Angst in den Zeiten der Cholera. 4 Bde. Berlin: Akademie Verlag, 2003 - Eke, Norbert Otto (Übersetzen im Vormärz. Hg. von Bernd Kortländer und Hans T. Siepe (Forum Vormärz Forschung. Jahrbuch 2007))

Distributed Resource Allocation and Management in Heterogeneous Networks - Schomaker, Gunnar

Uniform Budgets and the Envy-Free Pricing Problem - Briest, Patrick (Proceedings of the 35th InternationalColloquium on Automata, Languages and Programming (ICALP))

On the Approximability of Combinatorial Exchange Problems - Briest, Patrick; Krysta, Piotr; Babaioff, Moshe (Proceedings of the 1st International Symposium on Algorithmic Game Theory (SAGT))

Approximate Equilibria in Games with Few Players - Briest, Patrick; Goldberg, Paul W.; Roeglin, Heiko
We study the problem of computing approximate Nash equilibria (epsilon-Nash equilibria) in normal form games, where the number of players is a small constant. We consider the approach of looking for solutions with constant support size. It is known from recent work that in the 2-player case, a 1/2-Nash equilibrium can be easily found, but in general one cannot achieve a smaller value of epsilon than 1/2. In this paper we extend those results to the k-player case, and find that epsilon = 1-1/k is feasible, but cannot be improved upon. We show how stronger results for the 2-player case may be used in order to slightly improve upon the epsilon = 1-1/k obtained in the k-player case.

Quality Assurance of Grid Service Provisioning by Risk Aware Managing of Resource Failures - Battré, Dominic; Hovestadt, Matthias; Kao, Odej; Keller, Axel; Voss, Kerstin (Proc. Int. Conf. on Risks and Security of Internet and Systems)

Virtual Execution Environments and the Negotiation of Service Level Agreements in Grid Systems - Battré, Dominic; Hovestadt, Matthias; Kao, Odej; Keller, Axel; Voss, Kerstin (Proc. Int. DMTF Academic Alliance Workshop on Systems and Virtualization Management: Standards and New Technologies)
Service Level Agreements (SLAs) have focal importance if the commercial customer should be attracted to the Grid. An SLA-aware resource management system has already been realize, able to fulfill the SLA of jobs even in the case of resource failures. For this, it is able to migrate checkpointed jobs over the Grid. At this, virtual execution environments allow to increase the number of potential migration targets significantly. In this paper we outline the concept of such virtual execution environments and focus on the SLA negotiation aspects.